The Effect of E-WOM, Trust, and Website Quality on Consumers Purchase Intention at The Spa Secret in Batam City - Stephanie Stephanie; Inda Sukati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the effect of electronic word of mouth (E-WOM), trust, and website quality on the purchase intention of prospective consumers of The Spa Secret in Batam City. A quantitative approach with a descriptive method was employed. Primary data were collected through questionnaires distributed to 204 respondents selected using purposive sampling based on the Jacob Cohen formula. Prior to analysis, the research instrument was tested for validity and reliability, and the data were examined using classical assumption tests. Multiple linear regression analysis was applied to test the proposed hypotheses. The results indicate that E-WOM, trust, and website quality each have a positive and significant effect on purchase intention. Simultaneously, these three variables also demonstrate a significant influence on purchase intention. The coefficient of determination shows that E-WOM, trust, and website quality explain 47.6% of the variance in purchase intention, while the remaining percentage is influenced by other factors not examined in this study. These findings suggest that positive online reviews, a high level of consumer trust, and good website quality play an important role in enhancing the purchase intention of prospective consumers.